THE EFFORTS TO IMPROVE WRITING SKILL OF SECONDARY SCHOOL STUDENTS BY USING SNAKE AND LADDER GAME - Rini Widiastuti; Nafisah Endahati (Journal of English Language Teaching and English Linguistics, 2020)
This study aims to know the process of improving the writing skill of eight grade students at SMPN 14 Yogyakarta by using snakes and ladders game. The subjects of the study were the students of grade VIII B. They found difficulty in writing skills. The participants consisted of 32 students. The study was conducted in a classroom action research methodology. The data were collected through field notes, observation, interview and documentation. They were analyzed using descriptive qualitative. The result of the study shows that the process of teaching and learning in each cycle ran well by using snakes and ladders game. The indicators of achievement are students achieve higher the minimum standard score, use correct English structure, adopt a variety of English vocabulary, use appropriate punctuation, and write recount text appropriately. Those indicators of achievement obtain a successful result within 3 cycles. Based on the data analyses, there is an improvement in cycle 2 as many as 43.12% or at an average of 69.99. In cycle 3, the result increases up to 82.49 or 82.49%.